Validasi Bahan Ajar Kimia Lingkungan Pada Topik Pencemaran Lingkungan Dengan Pendekatan Etno-Stem - Henie Poerwandar Asmaningrum; Jusmiati Jusmiati; Jesi Jecsen Pongkendek; Marantika Lia Kristyasari (Jurnal Ilmiah Kanderang Tingang, 2022)
The purpose of this research is to develop environmental chemical materials on the topic of environmental pollution with an ethno-STEM approach in terms of its validity. This research is an ADDIE model development research. The population in this study were all class VII students of SMP Negeri 8 Merauke. The sample used is class VIIB. The sampling technique uses simple random sampling. The validity of the instrument can be proven by looking at the content, construction and criteria. This type of research data analysis is content validity. Validity is the focus on providing evidence for the elements in the measuring instrument and is processed by rational analysis. The results showed that the results of the validity test obtained an average score from the two validators with the four aspects of the assessment of 4.17 and 4.07, both in the good category. The validation average score in terms of material, presentation, language and graphic aspects was 4.29 (very good); 4.20 (very good); 4.00 (good) and 4.12 (good).